Vidobraženja istoriï ta kul’turi narodu v slovotvoreni: dopovidi XII Mižnarodnoï naukovoï konferenciï Komisiï zi slov’jans’kogo slovotvorenja pri Mižnarodnomu komiteti slavistiv (25–28 travnja 2010 p., Kiïv, Ukraïna) – Zbornik dvanajste konference Komisi: Ur. N. F. Klimenko, E. A. Karpilovs’ka. Naukove izd. Kiïv: Vidavnicij Dmitra Burago, 2010. 471 str. - Stramljič Breznik, Irena (Slavia Centralis, 2020)
The paper presents a collection of scientific papers created as part of the annual scientific meeting of the Commission for Slavic Word Formation, which took place in 2010 in Kiev.
Keywords: Commission for Slavic Word Formation; Kiev; collection of scientific papers; Vidobraženja istoriï ta kul’turi narodu v slovotvoreni; review